Comparison of segmental linear and angular momentum transfers in two-handed backhand stroke stances for different skill level tennis players - Wang, L.-H.; Lin, H.-T.; Lo, K.-C.; Hsieh, Y.-C.; Su, F.-C. (Journal of Science and Medicine in Sport, 2010)
The purpose of this study was to investigate the differences of momentum transfer from the trunk and upper extremities to the racket between open and square stances for different skill levels players in the two-handed backhand stroke. The motion capture system with twenty-one reflective markers attached on anatomic landmarks of the subject was used for two-handed backhand stroke motion data collection. Twelve subjects were divided into an advanced group and an intermediate group based on skill level. The three-dimensional linear and angular momentums of the trunk, upper arm, forearm, hand and racket were used for kinetic chain analysis. Results showed that all players with the square stance had significantly larger backward linear momentum contribution in trunk and upper arm than with the open stance (p < .05) irrespective of playing level. However, the external rotation angular momentum of the shoulder joint was significantly larger with an open stance than with a square stance (p = .047). Comparison of playing levels showed that the intermediate group performed higher linear momentum in three components of the trunk, upper arm backward linear momentum, and trunk right bending angular momentum than the advanced group significantly (p < .05). The advanced group reduces trunk linear movement to keep stability and applies trunk and linkage segment rotation to generate backhand stroke power. The advanced group also has a quick backswing for increasing acceleration and maintains longer in the follow-through phase for shock energy absorption. This information could improve training protocol design for teaching the two-handed backhand stroke and teaching players, especially beginners, how to make an effective stroke.